2000
DOI: 10.1161/01.cir.101.11.1297
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Implantable Defibrillator Study (CIDS)

Abstract: A 20% relative risk reduction occurred in all-cause mortality and a 33% reduction occurred in arrhythmic mortality with ICD therapy compared with amiodarone; this reduction did not reach statistical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
305
3
20

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,372 publications
(333 citation statements)
references
References 13 publications
5
305
3
20
Order By: Relevance
“…Three trials have been conducted for patients suffering from a cardiac arrest or life‐threatening VAs. These 3 trials have demonstrated a consistent result that an ICD implantation, rather than anti‐arrhythmic drugs, mostly amiodarone, significantly reduced the arrhythmic mortality or total mortality 45, 46, 47. Therefore, the current guidelines suggest an ICD implantation for (i) NICM patients who experience an aborted SCD, unexplained syncope, or hemodynamically unstable VT/VF, (ii) primary prevention for DCM patients with NYHA functional classes II‐III and a decreased LVEF of ≤35% in spite of ≥3 months of optimal pharmacological treatment, (iii) HCM patients who are classified as a high risk of SCD, (iv) patients with Chagas cardiomyopathy and an LVEF of <40%, and (v) ARVC patients with well‐tolerated sustained VTs, after balancing the risk of ICD therapy 20.…”
Section: Management Of Vt In Nicmmentioning
confidence: 88%
“…Three trials have been conducted for patients suffering from a cardiac arrest or life‐threatening VAs. These 3 trials have demonstrated a consistent result that an ICD implantation, rather than anti‐arrhythmic drugs, mostly amiodarone, significantly reduced the arrhythmic mortality or total mortality 45, 46, 47. Therefore, the current guidelines suggest an ICD implantation for (i) NICM patients who experience an aborted SCD, unexplained syncope, or hemodynamically unstable VT/VF, (ii) primary prevention for DCM patients with NYHA functional classes II‐III and a decreased LVEF of ≤35% in spite of ≥3 months of optimal pharmacological treatment, (iii) HCM patients who are classified as a high risk of SCD, (iv) patients with Chagas cardiomyopathy and an LVEF of <40%, and (v) ARVC patients with well‐tolerated sustained VTs, after balancing the risk of ICD therapy 20.…”
Section: Management Of Vt In Nicmmentioning
confidence: 88%
“…Since then, there have been remarkable technical advances. The ICD is now widely used in high‐risk patients based on evidence from RCTs that supports the use of ICDs for both primary and secondary prevention of SCA 30, 31, 32, 33, 34, 35. In particular, 3 randomized controlled trials evaluated the impact of ICD therapy for secondary prevention indications (Table 1).…”
Section: Randomized Controlled Trials Of Icds and Guidelinesmentioning
confidence: 99%
“…The last published RCT, the Canadian Implantable Defibrillator Study (CIDS), enrolled 659 patients between 1990 and 1997 32. Patients were included if they had any of the following: (1) documented VF, (2) out‐of‐hospital cardiac arrest requiring defibrillation or cardioversion, (3) syncope resulting from documented sustained VT, (4) documented sustained VT at a rate of ≥150 beats/min causing presyncope or angina with an LVEF ≤35%, or (5) syncope of undocumented etiology with subsequent documented spontaneous VT ≥10 seconds or sustained (≥30 seconds) monomorphic VT induced by programmed ventricular stimulation.…”
Section: Randomized Controlled Trials Of Icds and Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The AVID 110 , CIDS 111 and CASH 112 trials established that ICD improved survival compared with antiarrhythmic agents for secondary prevention of sudden cardiac death (SCD). Other randomised, multicentre studies including MADIT I 19 and II 113 , MUSTT 114 and the SCD‐HeFT 115 , established ICD therapy as effective for primary prevention of SCD in selected patient populations.…”
Section: Role Of Echocardiography In Therapeutic Interventionmentioning
confidence: 99%